Orwell's 1984 Revisited: Woke Vocabulary & Uncivil Discourse - Baker, Biff (Journal of Knowledge Management Practice, 2024)
Semantics study how language conveys meaning and is interpreted - examining word meaning, sentence meaning, pragmatics, and meaning representation. A shared understanding of word meanings is crucial for effective communication and social cohesion. Per Orwell’s 1984, political manipulation of language can shape public opinion and advance agendas through propagandistic euphemisms. Language manipulation undermines healthy discourse, critical thinking, and trust: recognizing these tactics is crucial for independent thinking. Understanding the impact of language is crucial for conflict resolution and promoting peace; clarity, empathy, and effective communication strategies enhance understanding. There is an ideological divide between academia and businesses, with a significant skew towards woke terminology and ‘far-left’ concepts. This "Woke Glossary" aims to bridge communication gaps and promote mutual understanding within academia and businesses via critiques. Fostering mutual understanding and effective communication should be our goals for promoting peace and cooperation, whereas woke terms often reinforce division using oppressor versus oppressed narratives.
Keywords: knowledge management; activism; affirmative action; anti-racism; allyship; cancel culture; cultural appropriation; Diversity, Equity, and Inclusion; empowerment; equality; equity; identity politics; implicit bias; intersectionality; marginalized communities; microaggressions; political correctness; privilege; safe spaces; social justice; social justice warriors; social consciousness; systemic oppression; systemic racism; white fragility; white privilege; white supremacy; woke; wokeness